1994
DOI: 10.1063/1.467967
|View full text |Cite
|
Sign up to set email alerts
|

Line shape analysis of the depolarized Rayleigh spectra of CS2/PS mixtures

Abstract: Raman line shape analysis in isotopic mixtures of liquid hydrogen and deuterium chloride J. Chem. Phys. 91, 2124 (1989); 10.1063/1.457072 Temperature and density effects on the collisioninduced depolarized Rayleigh line shapes of liquid carbon disulfide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
(3 reference statements)
2
6
0
Order By: Relevance
“…The most noticeable result is the displacement of the librational distribution to higher frequencies as the concentration of PS is increased. This corroborates the work of da Silveira et al, 1 Motivated by these results, another work of da Silveira et al 31 showed an ab initio determination of the C 6 H 6 -CS 2 cluster stabilization energy. The results of that work indicate the existence of weakly bound complexes between benzene and CS 2 .…”
Section: ͑4͒supporting
confidence: 88%
See 2 more Smart Citations
“…The most noticeable result is the displacement of the librational distribution to higher frequencies as the concentration of PS is increased. This corroborates the work of da Silveira et al, 1 Motivated by these results, another work of da Silveira et al 31 showed an ab initio determination of the C 6 H 6 -CS 2 cluster stabilization energy. The results of that work indicate the existence of weakly bound complexes between benzene and CS 2 .…”
Section: ͑4͒supporting
confidence: 88%
“…For the mixtures the range was kept about the same, but was translated to slower decays, as suggested in the literature. 1 For other parameters, since they were unknown prior to this work, the range was fixed to the limits plus 50% of similar systems. The randomly generated first population maps all the space formed by all variables with its 196 different individuals.…”
Section: ͑4͒mentioning
confidence: 99%
See 1 more Smart Citation
“…the distance between the centers of mass obtained was around 3.2 Å. 32 These results were also obtained by da Silveira et al, 33,34 in which they realized an ab initio calculation on C 6 H 6¯C S 2 cluster to determine the stabilization energies and the preferential configurations between the CS 2 -C 6 H 6 pair in this van der Waals complex. In that work, the authors also calculated the electronic density of the molecules CS 2 and C 6 H 6 when they were in the energy minimization configuration, establishing charge transfers between these molecules for all stable configurations.…”
Section: Resultssupporting
confidence: 68%
“…Traditionally, the dynamics of atomic and molecular liquids are studied by far-infrared ͑FIR͒ absorption spectroscopy 3,4 or by Rayleigh-Raman scattering, [5][6][7][8] that measure the Fourier transform of the one-time correlation function of the dipole moment and polarizability, respectively. In the thermal range below 300 cm Ϫ1 , the fluctuations in these bulk properties are associated with the same lowfrequency intermolecular motions.…”
Section: Introductionmentioning
confidence: 99%